Microbial burdens in disposable and nondisposable ventilator circuits used for 24 and 48 h in intensive care units. - Malecka-Griggs, B (1989)
One hospital sought to study the differences in using resterilizable permanent versus disposable ventilator circuits and changing the circuits on a 24-h versus a 48-h basis. Over a period of 13 months 656 condensate samples from 92 permanent and 72 disposable circuits were collected and plated by a loop dilution technique. Two samples were collected from the inspiratory limb (humidifier; tubing or nebulizer), and two were collected from the expiratory limb (tubing and trap) of each circuit. Contamination rates were higher for disposable circuits than for permanent circuits and for 48-h changes than for 24-h changes. Results of chi 2 testing by site indicated there was more contamination on the inspiratory and expiratory limbs each with use of disposable circuits than with the use of permanent circuits. The total results (chi 2 analysis) showed significantly greater microbial growth with the use of disposable circuits (permanent versus disposable, P less than 0.001) and extension of time to 48-h changes (24 h versus 48 h, P less than 0.05). In the experience of this hospital permanent circuits proved more advantageous from the standpoint of contamination risk and cost.